Increased LDL receptor by SREBP2 or SREBP2-induced lncRNA LDLR-AS promotes triglyceride accumulation in fish - Xiufei Cao; Wei Fang; Xueshan Li; Xiuneng Wang; Kangsen Mai; Qinghui Ai (iScience, 2022)
Summary: LDLR, as the uptake receptor of low-density lipoprotein, plays a crucial role in lipid metabolism. However, the detailed mechanism by which LDLR affects hepatic triglyceride (TG) accumulation has rarely been reported. Here, we found that knockdown of LDLR effectively mitigated PA-induced TG accumulation. Further analysis revealed that the expression of LDLR was controlled by SREBP2 directly and indirectly. On one hand, transcription factor SREBP2 activated the transcription of LDLR directly. On the other hand, SREBP2 indirectly regulated LDLR by increasing the transcription of lncRNA LDLR-AS in fish. Mechanism analysis found that LDLR-AS functioned as an RNA scaffold to recruit heterogeneous nuclear ribonucleoprotein R (hnRNPR) to the 5′ UTR region of LDLR mRNA, which stabilized LDLR mRNA at the post-transcription level. In conclusion, our study demonstrates that increased LDLR transcription and mRNA stability is regulated by SREBP2 directly or indirectly, and promotes hepatic TG accumulation by endocytosing LDL in fish.